2018
DOI: 10.1111/twec.12667
|View full text |Cite
|
Sign up to set email alerts
|

Do commodity price shocks weaken the financial sector?

Abstract: This paper investigates the impact of commodity price shocks on financial sector fragility. Using a large sample of 71 commodity exporters among emerging and developing economies, it shows that negative shocks to commodity prices tend to weaken the financial sector, with larger shocks having more pronounced impacts. More specifically, negative commodity price shocks are associated with higher non‐performing loans, bank costs and banking crises, while they reduce bank profits, liquidity and provisions to non‐pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 30 publications
4
38
1
Order By: Relevance
“…Barth et al (2009); and have shown that when bank supervisors or bank controlling shareholders abuse their power and get involved in corrupted activities, the likelihood of bank failure increases. Regarding export diversification, some studies have found that countries with relatively low export diversification are more susceptible to banking crises (Kinda et al 2018;Hausmann and Rojas-Suárez, 1996), other studies found that the level of financial development matters (Mathonnat and Minea, 2018). We find that controlling for these variables does not alter our baseline findings.…”
Section: B Including More Covariatescontrasting
confidence: 44%
See 1 more Smart Citation
“…Barth et al (2009); and have shown that when bank supervisors or bank controlling shareholders abuse their power and get involved in corrupted activities, the likelihood of bank failure increases. Regarding export diversification, some studies have found that countries with relatively low export diversification are more susceptible to banking crises (Kinda et al 2018;Hausmann and Rojas-Suárez, 1996), other studies found that the level of financial development matters (Mathonnat and Minea, 2018). We find that controlling for these variables does not alter our baseline findings.…”
Section: B Including More Covariatescontrasting
confidence: 44%
“…We control for the role of natural resource endowments in panels C and D. Kinda et al (2018) and Eberhardt and Presbitero (2018) have found that commodity price fluctuations can lead to banking crises. To capture this potential effect, we include in panel C the index of commodity prices as in Kinda et al (2018) and in panel D the total rents from natural resources as percentage of GDP. The results in these two panels are consistent with our baseline findings in Table 3.…”
Section: B Including More Covariatesmentioning
confidence: 99%
“…1 Notes: The chart shows "All Commodity Price Index" (2005 = 100); the index includes both fuel and nonfuel price indices. Source: International Monetary Fund (https://www.imf.org/external/np/res/commod/index.aspx) exposed to the commodity sector (Christensen 2016;Kinda, Mlachila, and Ouedraogo 2018). The diminished ability of banks to raise market funding would be particularly binding for banks starting with already relatively high levels of nonperforming loans, and could induce them to reduce bank lending to the economy even further (Gambacorta and Shin 2016).…”
Section: Figurementioning
confidence: 99%
“…The funding shock may end up affecting the credit supply of banks with lower deposits‐to‐assets ratios (Gatev and Strahan ), a channel that could be stronger in developing countries, where banks heavily rely on retail funding. Moreover, government arrears and weak revenue growth of commodity dependent firms may render them unable to service their loans, thereby worsening bank asset quality and eroding capital of banks highly exposed to the commodity sector (Christensen ; Kinda, Mlachila, and Ouedraogo ). The diminished ability of banks to raise market funding would be particularly binding for banks starting with already relatively high levels of nonperforming loans, and could induce them to reduce bank lending to the economy even further (Gambacorta and Shin )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation